Asia After The Crisis: Recovery and Reform - Anwar Ibrahim (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2014)
The lessons that can be drawn from the recent experience of East Asian economies appear to reinforce the argument that places the importance of market strengthening and government systems in the sustainability of economic recovery for which there are no short cuts. There a few key principles to keep in mind when we look at reform so that 10 years from now Asia does not find itself revisiting the unlearned lessons of 1997. The first is the practice of prudence and the concern for account- ability. Also it is important that the human element of this endeavour not be overlooked. Despite what some economists may say about the functioning of markets, social justice must remain one of the main purposes of govern- ments. And, constitutionalism which provides institutional reliability and accountability upon which sustained development depends.